The world of Justus Lipsius: A contribution towards his intellectual biography, edited by M. Laureys, Bulletin de l’Institut Historique Belge de Rome LXVIII, Bruxelles-Rome, nº 68, 1998, 452 pp. (Minerva, 2019)
Review: The world of Justus Lipsius: A contribution towards his intellectual biography, edited by M. Laureys, Bulletin de l’Institut Historique Belge de Rome LXVIII, Bruxelles-Rome, nº 68, 1998, 452 pp.